Pushing the boundaries of mechanical thrombectomy protocol for acute stroke management: two case reports - Želdakova , J.; Motiejūnas , G.; Jatužis , D. (Neurologijos seminarai, 2018)
Stroke is a severe disease causing long-term disability. Mechanical thrombectomy is an effective treatment method, which significantly improves patients’ outcomes if applied according to strict inclusion and exclusion criterias. However, more recent studies show, that mechanical thrombectomy may be a safe and effective method even if used in disregard of some classical criterias. In this article, two case reports are presented. In both cases, mechanical thrombectomy was successfully used beyond the protocol.
Keywords: stroke; treatment; mechanical thrombectomy